Hubungan di antara aset luaran dan tingkah laku antisosial belia yang menetap di projek perumahan rakyat Kuala Lumpur - Suzieyana Idris; Mohd Suhaimi Mohamad; Nor Ba’yah Abdul Kadir (Penerbit Universiti Kebangsaan Malaysia, 2020)
Youth problems are found to be on the rise as Malaysia is experiencing rapid millennium development. As youth are an important asset to a country’s future, this is particularly alarming. Thus, this issue requires attention and action from the community and responsible parties. Youth development efforts should be concentrating on the assets approach which will strengthen their capabilities and accentuate their self-potential while amplifying their intervention strategies to prevent antisocial behaviour. Therefore, this study aim to identify the relationship between external asset and antisosial behavior among youth in PPR Kuala Lumpur. Using a stratified random sample (two stages), a total of 450 inner-city youth has been systematically selected to complete a set of standardized questionnaires. The 25 Developmental Assets Questionnaire Malaysian version was used to measure developmental assets and Self-Reported Antisocial Behavior was used to measure antisocial behaviour. The result shows that only one subscale of external assets significantly correlated to serious antisocial behaviour and three subscales of external assets significantly correlated to violation antisocial behaviour. In short, this study shows that external asset should be taken into consideration when developing the youth intervention programs to reduce antisocial behaviours.